Impacto da exposição crônica ao fenol no metabolismo, fisiologia e resposta ao estresse de juvenis de Matrinxã (Brycon cephalus: Teleostei; Characidae) - Hori, Tiago Silvestre Fernandes (2005)
The contamination of the aquatic environment has been responsible for considerable losses on natural stocks of several marine and freshwater fish. Among the many classes of chemicals dumped in aquatic system, the phenols present a great harmful potential due to its many modes of action. These include: genotoxicity, haematotoxicity, immunotoxicity, citotoxicity, oxidative stress and action as endocrine disruptors. Several authors have also demonstrated phenols capability of altering fish metabolism. Moreover because of its lipophilicity, phenol has a high bioaccumulation potential and can, therefore, present a high risk to fish consumers. Matrinxa (Brycon cephalus) presents a great aquaculture potential because of it growth rate (1 kg/year) and its good acceptance for commercial feed. This fish also represents 7% of the total of fish consumed in the Amazonas state. The main objective of this work was to identify the metabolic, endocrine e cellular responses of Matrinxa (Brycon cephalus) exposed to sub lethal concentrations of phenol. In order to accomplish this, three experiments were conducted. The first one consisted in a toxicity test designed to establish de LC-50/96h of phenol to Matrinxa. After that the fish were exposed for 96 hours to 10% of Matrinxas LC-50. The objective of this experiment was to look into the metabolic alterations induced by phenol. Finally, we exposed Matrinxa for 96 hours to 1% and 10% of the LC-50 and at the end of the exposure submitted the fish to a handling stress. The second exposure experiment was designed to verify the responses of stress indicators (cortisol, glucose and HSP70) to phenol intoxication and also the possible effects of exposure in the ability of fish to respond to a second stressor. Phenol induced many alterations on Matrinxas metabolism. We could observe a general reduction of carbohydrate metabolism flowed by an increase in proteolysis. Both of these effects are likely to be a response to a higher metabolic demand, which was confirmed by an increase in oxidative metabolism. This data is contrary to the one found in case of pesticide intoxication, indicating there was no cellular anoxia. When considering cortisol and glucose phenol exposure did not elicit the classical stress response observed for other stressors. These results suggest that cortisol and glucose might not be the best indicators for chemical stress. A lower dose (0,2 ppm) clearly affected the fish ability to respond to a second stressor. The constitutive levels of HSP70 were reduced in gills and liver. In the gills a more lasting effect was observed. The handling stress did not affected HSP70 expression while starvation seemed to induce a generalized reduction on the levels this particular protein. When looking into the cellular stress response the higher dose (2,0 ppm) appears to be more toxic. The exposition to phenol also inhibited the characteristic ionic changes in response to stress. Phenol intoxication affects animal metabolism and this is likely to have effects on growth and survival. Moreover, the ability of these fish to respond to a second stressor is reduced in both organismal and cellular levels.